2015
DOI: 10.1589/jpts.27.441
|View full text |Cite
|
Sign up to set email alerts
|

Hip rotation range of motion in sitting and prone positions in healthy Japanese adults

Abstract: [Purpose] The aim of this study was to elucidate the difference in hip external and internal rotation ranges of motion (ROM) between the prone and sitting positions. [Subjects] The subjects included 151 students. [Methods] Hip rotational ROM was measured with the subjects in the prone and sitting positions. Two-way repeated measures analysis of variance (ANOVA) was used to analyze ipsilateral hip rotation ROM in the prone and sitting positions in males and females. The total ipsilateral hip rotation ROM was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
0
16
1
Order By: Relevance
“…It has been reported that internal and external hip rotational ROM have similar ranges, and these were 43.5º and 42.2º, respectively, in a healthy young Asian population 18 . The results of our study showed that internal hip rotational ROM was smaller than external hip rotational ROM, and internal hip rotational ROM in our study was also smaller than that in the previous study.…”
Section: Discussionmentioning
confidence: 73%
“…It has been reported that internal and external hip rotational ROM have similar ranges, and these were 43.5º and 42.2º, respectively, in a healthy young Asian population 18 . The results of our study showed that internal hip rotational ROM was smaller than external hip rotational ROM, and internal hip rotational ROM in our study was also smaller than that in the previous study.…”
Section: Discussionmentioning
confidence: 73%
“…Thus, it became clear that left and right differences can be easily detected by blocking visual information, in contrast to the difficulty detecting left and right differences in the OLST with respect to the Hip IR ROM laterality pattern before blocking visual information. Hip IR ROM was larger in females than in males 12 , 13 ) , and OLST was shorter with eyes closed than with eyes open 14 ) ( Table 1 ). The proportion of subjects with left and right differences in OLST increased significantly with eyes closed; left and right differences were prominent with eyes closed, and the proportion of subjects with left and right differences increased ( Table 2 ).…”
Section: Discussionmentioning
confidence: 96%
“…Kim et al 13 found that hip lateral rotation of Asian peoples was usually larger than that of Western peoples when they sit crossed-leg on the floor because sitting on the floor are common daily living in Asian peoples. Han et al 8 evaluated the angle of rotation of the hip joint of Japanese males who frequently sit crossed-leg.…”
Section: Discussionmentioning
confidence: 99%